FUNCTIONAL FOODS AND HEALTH: NUTRITIONAL STRATEGIES IN THE FORMULATION OF PASTA WITH ALTERNATIVE INGREDIENTS (REMUNOM, 2025)
Functional foods have been gaining prominence for promoting health benefits beyond basic nutrition, with an emphasis on the prevention of chronic non-communicable diseases. They are characterized by the presence of bioactive compounds with antioxidant, anti-inflammatory, hypoglycemic, and hypocholesterolemic properties. Among the ingredients of plant and animal origin, fish protein, a source of essential amino acids and polyunsaturated fatty acids, stands out; oat flour, rich in β-glucans with a cholesterol-lowering effect; passion fruit peel flour, composed of pectin and antioxidant phenolic compounds; avocado seed flour, with a high fiber content and antimicrobial properties; and quinoa, which provides high-biological-value protein, resistant starch, vitamins, and minerals. Incorporating these ingredients into breads, cookies, and pasta increases their nutritional value, improves glycemic response, and enhances sensory acceptance. This makes it a promising strategy for promoting health and diversifying the population's diet, aligning technological innovation with the demand for healthy and affordable foods.